ANALISIS FAKTOR PERILAKU KONSUMTIF PADA PEMAIN GENSHIN IMPACT GENERASI Z DI INDONESIA - Karina Sanggraeini Kusuma Winata; Ira Wikartika (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
The increase in digital spending in the video game sector has encou?raged the emergence of consumptive behavior among Genshin Impact players, particularly Generation Z. This study aims to analyze the influence of Peer Conformity, Financial Technology, Financial Literacy, and Locus of Control on the consumptive behavior of Generation Z Genshin Impact players. The research employed a quantitative approach by distributing questionnaires to 108 Generation Z Genshin Impact players, and the data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results indicate that peer conformity and financial technology  and locus of control have an impact  on consumptive behavior, while financial literacy has no significant signficant impact toward consumptive behavio